New prenylated coumarins from the stems of Toddalia asiatica. Issue 49 (15th June 2017) - Li, Wei; Zhang, Jun-Sheng; Huang, Jia-Luo; Jiang, Min-Hong; Xu, You-Kai; Ahmed, Abrar; Yin, Sheng; Tang, Gui-Hua
Abstract : Prenylated coumarins from Toddalia asiatica were established using spectroscopic data, X-ray, and ECD and specific optical rotation calculations. Abstract : Eight new prenylated coumarins (1a /1b, 2a /2b, and3–6 ) including two pairs of enantiomers (1a /1b and2a /2b ), a new phenolic acid derivative, methyl ( E )-3, 4-bis(4-hydroxyphenyl)-4-oxobut-2-enoate (7 ), and 33 known compounds (8–40 ) were isolated from the stems of Toddalia asiatica . Their structures were established from spectroscopic data and by chemical methods. The absolute configurations of two pairs of enantiomers (1a /1b and2a /2b ) were determined by X-ray diffraction analysis together with ECD and specific optical rotation calculations. The inhibitory effects of selected compounds against phosphodiesterase-4 (PDE4) were evaluated, and compounds12, 19, 21–23, 26, 34, and35 exhibited PDE4 inhibition activities with IC50 values less than 10 μM.